KOMODIFIKASI AGAMA DALAM PENGELOLAAN TAHFIZ AL-QUR’AN - Sangaji, Ruslan; Rasyid, Nirwana (Program Studi Pendidikan Agama Islam, 2023)
This paper aims to demonstrate the existence of the phenomenon of commodification of religion in the management of tahfidz al-Qur'an educational institutions and the impacts it has. This study uses a descriptive qualitative method and uses field data which is located in Bone Regency. Data was collected, processed and analyzed using the sociology of religion approach. The findings of this study show that the phenomenon of commodification of religion in the management of tahfidz al-Qur'an educational institutions occurs in line with the desire of institutional managers to see tahfidz institutions as more advanced and more developed. From an administrative point of view, managers of tahfidz institutions tend to increase the financing related to the management of tahfidz education, even though from one side the community or stakeholders have not fully accepted that learning the Koran must incur high costs. Learning and teaching the Koran, according to him, does not have to be exchanged for expensive financing. Besides commodification found at the administrative level, symptoms of religious commodification are also found at the distribution level of hafidz in society. The community's need for hafidz al-Qur'an has been quite significant so far, especially for the benefit of events or events at various scales, for example Musabaqah Tilawatil Qur'an on local and national scales. The impact of the emergence of commodification in the management of tahfidz al-Qur'an indirectly weakens the sacredness of religion, especially the Koran and erodes social values, especially the attitude of helping each other. The use value of the Qur'an as a human moral guide shifts from theological to economic paradigm.